A importância do registo vídeo gráfico no desenvolvimento do professor estagiário - Emanuel Jacinto Reneu da Silva Pereira Torres (2023)
The professional internship marks the transition from theoretical approaches to prac-tice. It's a process of countless lessons learned as a result of a reflective attitude and constant improvement, combined with supervised teaching practice. This report re-flects all the work carried out as a student teacher at Rio Tinto Secondary School, in a 12th grade class, as part of the Master's Degree in Teaching Physical Education in Primary and Secondary Schools. Topics such as the importance of planning, com-munication and leadership, the evaluation process, class management, the need to work in levels and the dissociation of the coach/teacher are particularly highlighted in this document. At the same time, the importance of video recording for the develop-ment of the student teacher was analyzed. All the 50' lessons were recorded during the month of February. Afterwards, the evaluation of the study was focused on the performance of the student teacher in class, which are the key aspects to be high-lighted, and how they allowed to adjust the subsequent practice. In this line of thought, the professional internship fostered growth as an author of what I say and what I do, using my own voice, acting as a person, and taking on the joy and respon-sibility of sharing the task of contributing to students development with them.